2016
DOI: 10.1007/s00167-016-4067-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after multiligament injured knees: medial versus lateral reconstructions

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 53 publications
(75 reference statements)
2
30
2
Order By: Relevance
“…1. Sixteen studies [14,16,23,25,[37][38][39][40][41][42][43][44][45][46][47][48] on single ACL injury (3004 patients) and 14 studies on MLKI [30,32,33,[49][50][51][52][53][54][55][56][57][58][59] (545 patients) were included in this meta-analysis of early vs delayed surgery. Details of these included studies are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Sixteen studies [14,16,23,25,[37][38][39][40][41][42][43][44][45][46][47][48] on single ACL injury (3004 patients) and 14 studies on MLKI [30,32,33,[49][50][51][52][53][54][55][56][57][58][59] (545 patients) were included in this meta-analysis of early vs delayed surgery. Details of these included studies are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of total meniscus injuries according to early vs delayed surgery was determined in 13 studies (2064 patients) on single ACL injury [23, 25, 37-44, 46, 47] and 4 studies (185 patients) on MLKI [49,[56][57][58]. The overall risk of meniscus tear in the delayed surgery group was significantly higher than that in the early surgery group, but this showed substantial heterogeneity (OR 1.73 [95% CI 1.1-2.73], p = 0.01; I 2 = 78%, p < 0.01), as did the L'Abbé plot (Fig.…”
Section: Risk Of Concomitant Meniscus Tearmentioning
confidence: 99%
“…Similarly, early PLC reconstruction (<3 weeks postinjury) had better results (72%) than those who underwent reconstruction thereafter (44%). 47 On average, 66%–79% patients KDIIIM injuries obtained good to excellent outcomes as compared to 44%–57% in case of KDIIIL injuries.…”
Section: Discussionmentioning
confidence: 95%
“…As with our material, some previous studies have reported good or excellent outcomes following multiligament injuries. 8,9,28 This finding is in part difficult to explain. Regarding the effect of cartilage and meniscal lesions, it has previously been shown that the patient-reported outcome for ACL injuries with concomitant meniscal lesions and superficial cartilage lesions is equal to that without such lesions.…”
Section: Discussionmentioning
confidence: 96%